Association between schizophrenia and violence among Chinese female offenders - Jun Wang (Nature Portfolio, 2017)
Abstract Little is known about the association between schizophrenia and violence in women in China. This study aimed to examine the association between schizophrenia and violence in Chinese female offenders. Fifty-two schizophrenia patients were identified from the female offenders who received forensic psychiatric assessments in 2011 in Hunan province, China. Using a propensity score matching method, 104 matched controls without psychiatric disorders were selected from female criminals in Hunan province. Violent offences and homicides were verified and recorded. The percentages of violent offences and homicides were significantly higher in female offenders with schizophrenia than in controls (78.8% vs. 30.8%, P < 0.001; 44.2% vs. 18.3%, P = 0.001, respectively). Multivariate logistic regression analyses revealed that diagnosis of schizophrenia, younger age at first offence, living in rural area and a lower education level were independently and positively associated with violent offences, while having a diagnosis of schizophrenia and lower education level were associated with homicides. There appears to be an independent and positive association between schizophrenia and violent offence in Chinese female offenders. Effective preventive approaches on violence in female schizophrenia patients are warranted.